Risk factor management over two decades in hospitalised patients with chronic limb-threatening ischaemia with and without diabetes mellitus - Sofia Bodinger; Tove Wikström; Anders Gottsäter; Stefan Acosta (Therapeutic Advances in Endocrinology and Metabolism)
Background: Chronic limb-threatening ischaemia (CLTI) causes high rates of amputation and mortality. Objectives: To compare incidence, management and prognosis in hospitalised patients with CLTI with and without diabetes mellitus (DM) in 2001 and 2023. A secondary objective was to compare adherence to global vascular guidelines on risk factors between patients with and without DM in 2023. Design: Retrospective study. Methods: Group differences were tested using the Mann–Whitney U test, independent sample t test or the Chi-square test, as appropriate. The effects of DM on major amputation or mortality at 1 year were evaluated in a multivariable logistic regression model according to a directed acyclic graph. Results: The incidence of hospitalisations for CLTI was reduced from 37.4 (95% confidence interval (CI), 33.3–41.6) in 2001 to 22.8 (95% CI, 19.7–25.8) per 100,000 person-years in 2023. The proportion of patients on full-dose oral anticoagulant therapy ( p  < 0.001) and lipid-lowering treatment ( p  < 0.001) increased significantly between the two time periods. In 2023, Wounds, Ischemia and foot Infection-classification in all patients with foot ulcers was documented in 6.9%. Anaemia was present at hospital admission in 67.0% and 52.5% of patients with CLTI with and without DM, respectively ( p  = 0.031). Endovascular therapy was performed more often in those with DM compared to those without DM ( p  = 0.004). Antiplatelet therapy ( p  = 0.008) and smoking cessation interventions ( p  = 0.033) were offered less often to those with DM. DM (odds ratio (OR), 1.7 (95% CI, 1.02–2.83)) was independently associated with increased mortality at 1 year, whereas period 2023 as opposed to 2001 (OR, 0.62 (95% CI, 0.38–0.99)) was associated with decreased mortality. Conclusion: The incidence of hospitalisation for CLTI appears to have been reduced, and medical care of patients with CLTI has improved prognosis. Nevertheless, there is still room for large improvements of secondary prevention care in patients with CLTI, particularly in those with DM.